THE IMPACT OF NURSE-LED FALL PREVENTION PROGRAMS ON REDUCING FALL-RELATED INJURIES - Majed Salah Marzouq Al-Harbi, Mutaib Abdualrhman Mukhlid Alotaibi, Ashwaq Ali Musa Al Moalwy, Naif Abdullah Abdalrhman Alharbi, Maha Mahdi Hazaa Alanazi, Faisal Faleh Baruk Alharbi, Ashwaq Sultan Alsaluli, Abdulrahman Abdulla Alsahli; Abdulmajeed Hajed Alotaibi, Mahal Bander Alotaibi, Mohammed Ibrahim Alreshoodi, Rasheed Mohammed Alotaibi, Itidal Mohammed A Alnami, Mona Ali Al Bishi, Hatem Saud Alarifi (Chelonian Research Foundation, 2022)
Falls among the elderly can be avoided, and nurse-led fall prevention initiatives are effective and feasible ways to stop falls. The purpose of this systematic review was to learn more about the impact of nurse-led fall prevention initiatives for senior citizens. This literature search was done using the CINAHL, MEDLINE, Eric, Science Direct, and Google Scholar databases. The Preferred Reporting Items for Systemic Reviews and Meta-Analysis were followed as a framework for reporting this research. The papers' quality rating and degree of evidence were assessed using the Johns Hopkins Nursing Evidence-Based Practice, and a matrix review method was utilized to extract the data. The duties of nurses included assessing patients, educating them, administering exercise regimens, and following up with patients after interventions. Five studies found a reduction in fall rates and fall events, whereas three studies found alterations in patient behavior. Positive results were obtained from fall prevention programs that included teaching components tailored specifically for nursing staff and older persons. The outcomes of patients are greatly improved by nursing staff, and the benefits of a fall prevention program that aims to lower the rate of falls that cause injury and improve participant behavior might be maximized. Keywords: nursing-led, older adults, education, falls, prevention, rates, and literature review